2005
DOI: 10.1038/sj.jp.7211354
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Oral Commissure Defect: A Complication of Prolonged Endotracheal Intubation

Abstract: A number of complications during and following endotracheal intubation of infants are well described in the literature. We describe a rare case of an oral commissure defect acquired from prolonged endotracheal intubation in a ventilator-dependent preterm infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This case illustrates an important clinical feature of upper lip PU arising from endotracheal tube tension in a preterm neonate. In the two published cases on neonatal PU due to endotracheal tube tension, PU occurred at 28–72 days after birth . The neonates in these cases were born at <29 weeks of gestation and had very low‐birthweight (<1200 g).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case illustrates an important clinical feature of upper lip PU arising from endotracheal tube tension in a preterm neonate. In the two published cases on neonatal PU due to endotracheal tube tension, PU occurred at 28–72 days after birth . The neonates in these cases were born at <29 weeks of gestation and had very low‐birthweight (<1200 g).…”
Section: Discussionmentioning
confidence: 99%
“…Elastic tape, which is flexible but has strong tension, is used for fixation in the present NICU, but this strong tension may be associated with the development of PU. Kahn and Spinazzola reported that routine use of endotracheal tube holder can protect the lip from pressure …”
Section: Discussionmentioning
confidence: 99%
“…On day 72 after a 3.5-mm endotracheal tube (ETT) intubation, a circular lesion was discovered on the left side of the mouth while replacing the ETT holder. The lesion, which occurred in the oral commissure area, was clean and smooth, without active bleeding, with minimal reactive inflammation [22].…”
Section: Acquired Oral Commissure Defectmentioning
confidence: 99%
“…Various complications of orotracheal intubation in infants have been documented in the literature (Tables 1 and 2), including acute [13141516] and chronic trauma [17] to the hypopharyngeal structures, systemic [181920], and local [21] side effects, and deleterious effects on oral development [22232425]. Delayed eruption, ectopic impaction, and tooth malformation following orotracheal intubation are reportedly caused by displacement and localized trauma to the tooth germ [42627].…”
Section: Introductionmentioning
confidence: 99%
“…These complications may occur throughout the respiratory system locally as apnea, oropharyngeal aspiration, atelectasis, pneumothorax, pneumonia, vocal cord edema and perforation, granuloma formation, subglottic stenosis, tracheitis, and hemorrhage. Hypoxia, bradycardia, hypertension, and infection are systemic complications related to OTI 4‐6 . Specifically, the OTI may cause detrimental effects on oral development during the acute phase or later by damaging the alveolar crest and developing tooth germs in the anterior region 7 .…”
Section: Introductionmentioning
confidence: 99%